The uptake and costs of guidelines for stroke in a district of southern England. Issue 5 (October 1997) - Wolfe, C D; Stojcevic, N; Rudd, A G; Warburton, F; Beech, R
Abstract : STUDY OBJECTIVE: To assess the impact of guidelines for stroke management on the utilisation of services by patients and the cost consequences of implementation. DESIGN: Prospective audit. SETTING: District health authority in southern England. PATIENTS: A total of 468 live non-comatose stroke patients registered between November 1991 and May 1993. MAIN OUTCOME MEASURES: A comparison between the three, six month periods for investigations performed and rehabilitation received and their associated costs. RESULTS: The appropriateness of the use of investigations improved over time to between 88 and 92% except for computed tomography (CT) (24%). Younger, more severely impaired patients in a medical bed were more likely to have CT. Overall levels of rehabilitation were low. There was no change in use of physiotherapy (61% to 63%), a significant increase in occupational therapy (26% to 39%) and a non significant change in speech therapy (34% to 25%) over time. Guideline introduction caused a modest 23 Pounds increase in costs per patient in the 2nd six months and 41 Pounds in the 3rd six months but this sum could rise to 430 Pounds per patient if full implementation of the guidelines occurred which is still only around 13% of the costs of nursing care while in hospital. CONCLUSIONS: This 18 month aduit shows only modest changes in practice compared with guidelines, and overall levels of rehabilitation were low. The costs of full implementation seem considerable, but in fact constitute only a small proportion of nursing care costs.